Antibody-dependent passive protection of mucosal surfaces - Mestecky, Jiri (Human vaccines & immunotherapeutics, 2022)
Extensive experiments performed mostly in a variety of animal models convincingly demonstrated the protective effect of polyclonal or monoclonal antibodies administered by the mucosal route. Because of the independence of the mucosal and systemic compartments of the immune system, antibodies from the circulation are not effectively transported in sufficient quantities into external secretions. Nevertheless, local application of antibodies of the desired specificity to mucosal membranes of the respiratory, gastrointestinal, and female genital tracts protected experimental animals from the subsequent challenge by corresponding viral or bacterial pathogens. Thus, generation of monoclonal antibodies of desired specificity and the selection of delivery systems to extend their otherwise short survival on some mucosal surfaces are essential aims of their usability in humans for the effective prevention of mucosally acquired infectious diseases.
Keywords: IgA; monoklonální protilátky; sliznice; Antibodies, Monoclonal; Female; Animals; ženské pohlaví; Immune System; Mucosal immunity; Gastrointestinal Tract; passive protection; monoclonal antibodies; zvířata; Immunity, Mucosal; slizniční imunita; gastrointestinální trakt; imunitní systém; Mucous Membrane